0=-8(p-5)

Simple and best practice solution for 0=-8(p-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0=-8(p-5) equation:


Simplifying
0 = -8(p + -5)

Reorder the terms:
0 = -8(-5 + p)
0 = (-5 * -8 + p * -8)
0 = (40 + -8p)

Solving
0 = 40 + -8p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '8p' to each side of the equation.
0 + 8p = 40 + -8p + 8p
Remove the zero:
8p = 40 + -8p + 8p

Combine like terms: -8p + 8p = 0
8p = 40 + 0
8p = 40

Divide each side by '8'.
p = 5

Simplifying
p = 5

See similar equations:

| 8x+3=-2x-5 | | 126x-5x=5x+16 | | x^2+6x+2=5 | | [3x+7]=7x-21 | | 56-2x=9x+20 | | -3x+5=5x-6 | | 4x+2x+x=8 | | 2y^2+12y=80 | | b^2-10b-16=0 | | 18y^2-57y=-35 | | 8x+3=2x-5 | | 21x^2+13x=8 | | x^2+10=-7 | | 4x-12=3x-6 | | 4x-12=-3x-6 | | -3x+5=1x-5 | | y^4-13y^3=42y^2 | | 6=.5+2 | | 2m-3+m=15 | | 24n(n-1)=0 | | x^2-17x+84=0 | | 3x^2-x-6=0 | | -12x-4(5+10x)=11(-3x+12) | | 9x=5x+9x-15 | | c(c-17)=0 | | 3x+6=2x+9 | | 4=-0.8 | | 5x+5=5x+x+2 | | 10x+6=6x-8+10x-16 | | 12*11-20= | | 16x-9=5x+12x-20 | | 10x+9-11-x=-2(2x+4)-3(2x-2) |

Equations solver categories